Transcriptional engineering of Escherichia coli K4 for fructosylated chondroitin production. (16th July 2013) - Wu, Qiulin; Yang, Aihua; Zou, Wei; Duan, Zuoying; Liu, Jie; Chen, Jian; Liu, Liming
Abstract : The capsule polysaccharide (CPS) of Escherichia coli K4 (K4CPS) is identical to fructosylated chondroitin, which can be modified to chondroitin sulfate, a commercially valuable biopolymer commonly used in pharmaceutical applications. In this study, we homologously overexpressed the transcriptional regulator SlyA to enhance the expression of K4 capsule gene cluster and production of CPS. The iTRAQ quantificaton of proteomics revealed 77 up‐regulated proteins and 143 down‐regulated proteins in E. coli THslyA. Most enzymes of glycolysis and citrate cycle pathway were weakened, while proteins associated with K4CPS synthesis were up‐regulated, showing a shift of carbon flux from cell growth to K4CPS production. Further, the production of K4CPS by the recombinant strain was 1 and 2.6 g/L in a shake flask and 7‐L batch bioreactor, which was 1.85‐ and 1.53‐fold higher than that of the wild‐type strain, respectively. Thus, this study provides a viable strategy for improving the production of K4CPS through a transcriptional‐level manipulation. © 2013 American Institute of Chemical Engineers Biotechnol. Prog ., 29:1140–1149, 2013